1991
DOI: 10.1007/bf00436120
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of keratinophilic fungi from soil in Malaysia

Abstract: Two hundred and thirty soil samples from different localities were examined for the presence of geophilic keratinophilic fungi. Six species namely Microsporum gypseum--34 isolates, Chrysosporium keratinophilum--29, C. tropicum--20, Keratinophyton terreum--4, Trichophyton terrestre--8 and Chrysosporium species--3--were isolated. Most of these fungi were recovered from garden, field and river bank soil. The importance of these findings is briefly discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Naturally, these plant and soil fungi will be on the body and feathers of the swiftlets, and possibly transferred to the EBN produced. One of the fungal species, Chrysosporium sp., which was reported in a study on the fungi isolated from Malaysian soil sample was also found in EBN samples in this study (Soon 1991). Although these species are not known to cause severe infections in immunocompetent humans, they may cause infections in animals.…”
Section: Discussionsupporting
confidence: 53%
“…Naturally, these plant and soil fungi will be on the body and feathers of the swiftlets, and possibly transferred to the EBN produced. One of the fungal species, Chrysosporium sp., which was reported in a study on the fungi isolated from Malaysian soil sample was also found in EBN samples in this study (Soon 1991). Although these species are not known to cause severe infections in immunocompetent humans, they may cause infections in animals.…”
Section: Discussionsupporting
confidence: 53%
“…The occurrence and distribution of keratinophilic and related fungi of different mud habitats have been investigated (Hassan 1982(Hassan , 1991Mangiarotti and Caretta 1984;Miyoshi et al 1985;Hassan and Batko 1986;Chabasse 1988;Hassan and Shoulkamy 1991;Soon 1991;Abdullah and Dina 1995;Ulfig et al 1996Ulfig et al , 1997Ali-Shtayeh et al 1999;Ali-Shtayeh and Rana 2000). *Corresponding author.…”
Section: Introductionmentioning
confidence: 98%